The RNA-binding protein hnRNPA2 regulates β-catenin protein expression and is overexpressed in prostate cancer - Stockley, Jacqueline (Landes Bioscience, 2014)
Introduction The RNA-binding protein hnRNPA2 (HNRNPA2B1) is upregulated in cancer, where it controls alternative pre-mRNA splicing of cancer-relevant genes. Cytoplasmic hnRNPA2 is reported in aggressive cancers, but is functionally uncharacterized. We explored the role of hnRNPA2 in prostate cancer (PCa). Methods: hnRNPA2 function/localization/expression in PCa was determined using biochemical approaches (colony forming/proliferation/luciferase reporter assays/flow cytometry/immunohistocytochemistry). Binding of hnRNPA2 within cancer-relevant 3′-UTR mRNAs was identified by bioinformatics. Results: RNAi-mediated knockdown of hnRNPA2 reduced colony forming and proliferation, while hnRNPA2 overexpression increased proliferation of PCa cells. Nuclear hnRNPA2 is overexpressed in high-grade clinical PCa, and is also observed in the cytoplasm in some cases. Ectopic expression of a predominantly cytoplasmic variant hnRNPA2-ΔRGG also increased PCa cell proliferation, suggesting that cytoplasmic hnRNPA2 may also be functionally relevant in PCa. Consistent with its known cytoplasmic roles, hnRNPA2 was associated with 3′-UTR mRNAs of several cancer-relevant mRNAs including β-catenin (CTNNB1). Both wild-type hnRNPA2 and hnRNPA2-ΔRGG act on CTNNB1 3′-UTR mRNA, increasing endogenous CTNNB1 mRNA expression and β-catenin protein expression and nuclear localization. Conclusion: Nuclear and cytoplasmic hnRNPA2 are present in PCa and appear to be functionally important. Cytoplasmic hnRNPA2 may affect the cancer cell phenotype through 3′-UTR mRNA-mediated regulation of β-catenin expression and other cancer-relevant genes.